Territori i relacions institucionals a la Catalunya del Sis-cents. Tres estudis de cas a partir dels processos de la Visita del General de Catalunya. - TORRA, RICARD (Scripta, 2019)
This article studies three different cases judged by the Visita of the Generality of Catalonia within the first decades of the 17th Century. Thanks to its study, we can comprehend the role developed by the Visita in controlling the actions of the public officers of the Generality of Catalonia during the whole century, how the Generality was established around the territories of the Principality of Catalonia and the political relations amongst the major institutions in Catalonia in the mid-1650's. The first two cases that we want to analyse took place during the inspection conducted by the Visita of the Generality of Catalonia of 1629-1630 within the tax district of Vilafranca de Conflent, which focused their attention on its public officers. The third case, which took place after the conclusion of the Reaper's War (1640-1652), pays particular attention to the relation between the diputats and the oïdors de comptes of the Generality of Catalonia of 1654-1656, the commanders of the institution, and the visitadors of 1654-1655.